Plasma Level of IL-4 Differs in Patients Infected with Different Modern Lineages of M. tuberculosis. (25th September 2012) - Mihret, Adane; Bekele, Yonas; Loxton, Andre G.; Aseffa, Abraham; Howe, Rawleigh; Walzl, Gerhard
Abstract : Epidemiological evidence from tuberculosis outbreaks revealed that some genotypes of M. tuberculosis are more transmissible and capable of causing disease than others. We analysed the plasma cytokine levels of pulmonary tuberculosis patients infected with different strains of M. tuberculosis to test the hypothesis that immune responses would be linked to the bacterial genotype. Spoligotyping was carried out for genotyping, and we used Luminex technology to measure 17 cytokines (EGF, fractalkine, GM-CSF, IFN- γ, IL-1, IL-10, IL-12, IL-17, IL-4, IL-7, IL-9, IP-10, MCP-1, MCP-3, MIP-1 β, TNF, and VEGF) from plasma samples of tuberculosis patients. The levels of IL-12 (p40), IL-4, IL-7, and MIP-1beta were higher in patients infected with lineage 3, however, it was only IL-4 which showed statistically significant difference (P < 0.05 ) between lineage 3 and lineage 4. We further grouped the lineages into families (CAS, H and T families), and we found that the plasma level of IL-4 was significantly higher in patients infected with the CAS family (P < 0.05 ) in comparison with T and H families. However, there was no difference between T and H families. Therefore, the higher level of IL-4 in lineage 3 families might indicate that possible differences in the response elicited from host depend on strain lineages in the studied population.